2015 International School on Nonsinusoidal Currents and Compensation (ISNCC) 2015
DOI: 10.1109/isncc.2015.7174700
|View full text |Cite
|
Sign up to set email alerts
|

Online network impedance identification with wave-package and inter-harmonic signals

Abstract: In power system analysis the main supply at a point of common coupling (PCC) is often presented by its Thevenin or Norton equivalent. In most cases these models adequately define the electrical characteristics of a PCC and are commonly used for power flow evaluations, fault estimations, as well as stability and power quality assessments. To determine the equivalent impedance of a PCC through analytical calculation or simulation precisely may be challenging due to the complexity and time varying nature of power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The voltages and currents of the first interval where the switch is open (subscript 1) and the second interval where the load is pulsed by the switch (subscript 2) are transformed into the frequency domain with FFT-algorithms. In the frequency domain the complex spectra of the grid impedance G ( ) can be calculated as follows: Strategies to excite the grid with pulsed current sequences can be found in [16], [17] and [18]. With periodic pulse signals the grid impedance can be precisely measured at specific frequencies.…”
Section: Basic Principle Of Applied Grid Impedance Measurement Methodsmentioning
confidence: 99%
“…The voltages and currents of the first interval where the switch is open (subscript 1) and the second interval where the load is pulsed by the switch (subscript 2) are transformed into the frequency domain with FFT-algorithms. In the frequency domain the complex spectra of the grid impedance G ( ) can be calculated as follows: Strategies to excite the grid with pulsed current sequences can be found in [16], [17] and [18]. With periodic pulse signals the grid impedance can be precisely measured at specific frequencies.…”
Section: Basic Principle Of Applied Grid Impedance Measurement Methodsmentioning
confidence: 99%
“…In case of absence of control parameters involved in analytical derivation of Norton, small-signal impedance modeling is an alternative way of modelling parameter estimation. In Reference [19], Authors excited the system with short sequences of current signals and identified its impedance by constructing the relationship between corresponding voltage and current characteristics. A study in Reference [20] is conducted using this method to analyze the terminal characteristics of a MMC (Modular Multilevel Converter) system.…”
Section: Introductionmentioning
confidence: 99%